Desenvolvimento de uma plataforma de força multiaxial para instrumentação biomédica - Urquiza, Marcelle Alencar (2005)
The evolution of techniques for the development of equipment capable of translating the results taken from a diverse and complex set of tasks carried out by the human body, has become an important item on the scientific communities agenda. Within the context of such equipment, the force plate has shown itself capable of being implemented for the task of measuring phenomena, which before could only be observed visually. This work has as its objective to describe and develop an extensometric, multiaxial force plate, for use as a biomedical assistance apparatus. Sensors for the detection of forces such as strain gauges were used and fixed in predetermined areas on the four transducers, which are an integral and fundamental part of the force plate apparatus. The cell design was completed using geometry capable of coupling with the minimum of interference the two different forces present within the structure. In this manner it is possible to quantify the forces in three orthogonal directions. The prototype developed can be utilized, for example as an evaluation tool for both gait and stability research. In parallel to the development of the force plate, equipment for carrying out the conditioning and digitalization of signals originating from the load cells was designed and constructed. The control of the acquisition processes as well as the processing of signals received from the force plate is carried out by the use of a specific applicative, which makes the quantitative values of the forces, strength and momentum available, allowing for the calculation of the parameters used for the respective biomedical evaluations, especially those dealing with the oscillation of the human body in an erect near static posture. Still further the applicative provides a confidence ellipse obtained from the stability evaluations carried out along with the coordinates of pressure center and standard stability indexes obtained instantaneously.